Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan Pada PT. Vengoz Busana Indonesia - Sairoh Sairoh; Hendra Kurniawan; Syabrinildi Syabrinildi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the influence of the work environment and employee work discipline on employee job satisfaction at PT. Vengoz Busana Indonesia. The population of this research is employees of PT. Vengoz Busana Indonesia which consists of 30 employees of PT. Vengoz Busana Indonesia Sample determination was taken using saturated samples. This research uses primary data by collecting data through questionnaires distributed to PT employees. Vengoz Busana Indonesia. This research uses quantitative methods and the data collected is processed with SPSS 25. The results of the research show that partially the work environment influences employee job satisfaction with t count (6.767) > t table (2.048) with a significant value of 0.000<0.05, partially discipline work has an effect on employee job satisfaction with t count (3.059) > t table (2.048) with a significant value of 0.005 <0.05. And simultaneously the work environment and work discipline have a significant influence on employee job satisfaction with a calculated F of 126.450 > F table of 3.35 with a significant value of 0.000 < 0.05.